'This is my home country or something in-between' – Finnish-Somali youth sharing their experiences through performative narratives. (2nd November 2012) - Oikarinen-Jabai, Helena
In this article I will focus on a workshop run with a group of youth mostly from Somali backgrounds. The workshops were run in cooperation with Youth's Multicultural Living Room and Youth Department of the City of Helsinki. The workshops are part of my larger research project 'A Finn, a Foreigner or a Transnational Hip-hopper?'. The study was conducted within the framework of participatory research, and examines the identification negotiations of second-generation Finnish immigrant youth. In the research I apply ethnographic methods, in particular, those of participatory and performative design, which I will briefly discuss here. In the workshops at hand it was noted that the participating youth placed themselves on borders and liminal spaces, especially because of the racism and prejudices they frequently encounter. Therefore, this article will concentrate on the topics of belongings, Finnishness and transnational identifications as represented in the words and visual narratives of the participants. I give space here to their own words and images they have produced.Finally, I will outline the kinds of horizons the observed ambivalence can create.